Behaviors of household in pork consumption in Hung Yen province - Nguyen Thi Duong Nga (2016)
Pig production provides livelihood for more than 4 million rural smallholders in the country. Understanding pork consumption behavior is thus important for upgrading the pig value chains in Vietnam. The study is conducted with 208 households in Hung Yen. The results show that annual per capita pork consumption is about 26kg. Consumers prefer fresh meat, which is from healthy pigs, and react quite strongly with pork quality. Less than 1% of respondents trust that pork sold in market is safe, implies that the pig value chain, especially the formal/modern retailing sector, has not yet gained consumer trust. In the context of economic integration, smallholder pig value chain must be upgraded to be competitive with cheap imported pork. Several potential implications are drawn for upgrading the pig value chains, focusing on both production organization and macro policy in short run.